An unusual recurrence of pruritic creeping eruption after treatment of cutaneous larva migrans in an adult Ghanaian male: a case report with a brief review of literature - Quashie, Neils Ben (Pan Afr Med J, 2015)
The hookworm related Cutaneous Larva Migrans is a common disease present in the tropic and subtropical areas of the world. The disease is self limiting and would naturally resolve within weeks. However, an unusual recurrence of the disease in a Ghanaian male after standard treatment was observed and is herein reported. A 52 year old Ghanaian male of Akan dissent was diagnosed with Cutaneous Larva Migrans in a clinic in Accra, Ghana. Symptoms of the disease persisted for three days after treatment with a 400mg single dose Albendazole and was only resolved after re-dosing with 400 mg daily of the same drug for three days. Two months post-treatment, the usual pruritic creeping eruption typical with the disease re-appeared even though the victim has not been re-exposed to any possible larva contaminated source. This could possibly be a case of hookworm- related larva resistance to a standard anti-helminthic therapy and host immunity.